Genistein and exercise modulated lipid peroxidation and improved steatohepatitis in ovariectomized rats - Namthip Witayavanitkul; Duangporn Werawatganon; Maneerat Chayanupatkul; Naruemon Klaikeaw; Sompol Sanguanrungsirikul; Prasong Siriviriyakul (BMC, 2020)
Abstract Background The prevalence of nonalcoholic steatohepatitis (NASH) in menopausal women is increasing, but current treatments have not been proven effective. The objective of this study was to investigate the treatment effects of genistein and running exercise in ovariectomized (OVX) rats with NASH. Methods Thirty-six female Sprague-Dawley rats were divided into 6 groups, control; OVX with standard diet; OVX with high fat and high fructose (HFHF) diet for 4 weeks; OVX with HFHF and genistein treatment (16 mg/kg BW/day) for 5 weeks (OVX + HFHF+GEN); OVX with HFHF and moderate intensity exercise for 5 weeks (OVX + HFHF+EX); OVX with HFHF and combined treatments (OVX + HFHF+GEN + EX). Serum interleukin-6 (IL-6) levels, hepatic free fatty acid (FFA), hepatic glutathione (GSH), and hepatic malondialdehyde (MDA) levels were measured. Liver histology was examined to determine NASH severity. Results OVX + HFHF group had the highest levels of hepatic FFA compared with OVX and control groups (5.92 ± 0.84 vs. 0.37 ± 0.01 vs. 0.42 ± 0.04 nmol/mg protein, respectively, p < 0.01). Serum IL-6 levels were significantly elevated in both OVX and OVX + HFHF groups as compared with controls (112.13 ± 6.50 vs. 121.47 ± 3.96 vs. 86.13 ± 2.40 pg/mL, respectively, p < 0.01). In OVX + HFHF group, hepatic MDA levels were higher, while GSH levels were lower than in OVX and control groups (MDA; 0.98 ± 0.04 vs. 0.82 ± 0.02 vs. 0.78 ± 0.03 nmol/mg protein, and GSH; 46.01 ± 0.91 vs. 55.21 ± 1.40 vs. 57.94 ± 0.32, respectively; p < 0.01 for both). Comparing with OVX + HFHF group, rats that received genistein, exercise and combined treatments demonstrated an improvement in liver histopathology, decreased levels of hepatic FFA (1.44 ± 0.21 vs. 0.45 ± 0.04 vs. 0.49 ± 0.05 nmol/mg protein, respectively, p < 0.01), serum IL-6 (82.80 ± 2.07 vs. 83.47 ± 2.81 vs. 94.13 ± 1.61 pg/mL, respectively, p < 0.01), and hepatic MDA (0.80 ± 0.03 vs. 0.76 ± 0.02 vs. 0.76 ± 0.03 nmol/mg protein, respectively, p < 0.01). Conclusions Genistein and moderate intensity exercise were effective in reducing the severity of NASH in OVX rats through the reduction in liver inflammation, oxidative stress and liver fat contents.